Conditioning regimens in pediatric myeloid malignancies undergoing allogeneic HSCT: a comparative single-center study - Marcu, Andra D.; Jercan, Cristina G.; Bica, Ana M.; Serbanica, Andreea N.; Radu, Letitia E.; Avramescu, Irina; Mocanu, Anda; Niculita, Oana O.; Popa, Delia C.; Jardan, Cerasela; Dragomir, Mihaela; Colita, Andrei; et al. (Frontiers in Oncology, 2025)
IntroductionOptimal conditioning regimen for pediatric myeloid malignancies is still subject for debate. This single-center retrospective study compares the efficacy and toxicity profiles of three conditioning strategies, myeloablative conditioning (MAC), reduced-toxicity conditioning (RTC), and reduced-intensity conditioning (RIC), in 59 pediatric patients with myeloid malignancies undergoing allogeneic hematopoietic stem cell transplantation (HSCT).MethodsPrimary objectives evaluated graft versus host disease (GvHD), relapse, overall survival (OS), disease-free survival (DFS), and mortality causes. Secondary endpoints assessed early complications such as mucositis, engraftment kinetics, viral reactivation, and hospitalization duration. A subgroup analysis compared fludarabine- and clofarabine-based RTC regimens.ResultsRTC was associated with significantly lower transfusion needs, faster platelet engraftment and shorter hospitalization. Viral reactivations were more common in RTC and RIC, yet viral control, particularly CMV clearance, seemed more effective in RTC. While one-year OS and DFS were generally comparable across regimens, RTC showed a numerically higher OS, with a possible negative influence on relapse rate for children under 10 years old. Severe acute GvHD was similar across groups, but chronic GvHD tended to occur more frequently in RIC. CR status appeared to influence relapse and mortality patterns, with AML patients transplanted in CR1 experiencing significantly better OS and DFS. Subgroup analysis within RTC (clofarabine vs. fludarabine) revealed promising trends toward improved OS, lower acute GvHD, and reduced relapse-related mortality when using clofarabine.DiscussionsThese findings support the use of individualized conditioning strategies in pediatric myeloid malignancies, with RTC emerging as a potentially balanced approach for selected cases.